2010
DOI: 10.1111/j.1365-2303.2009.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology and flow cytometry immunophenotyping of non‐Hodgkin lymphoma: can we do better?

Abstract: FNAC/FC is a fundamental tool in the diagnosis and classification of NHL but the exiguity of diagnostic material and other technical and clinical limitations will probably continue to limit further improvement of the technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
3
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 35 publications
2
89
3
1
Order By: Relevance
“…Furthermore, we were able to perform cytogenetic analysis for MYC, IGH-BCL-2, and BCL-6 rearrangement in all our DLBCL cases to identify aggressive subtypes (presence of IGH-MYC, MYC rearrangement, or concomitant presence of MYC and IGH-BCL-2 and/or BCL-6 rearrangements) (33,34). We also demonstrate subclassification of low-grade NHL, using a combination of immunohistochemistry on cell block and flow cytometry into CLL-SLL, follicular lymphoma, mantle cell lymphoma, and marginal zone lymphoma (35)(36)(37). Moreover, adequate material was available after this multimodality testing approach for IGH-TCR gene rearrangement studies by polymerase chain reaction, when this was required.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, we were able to perform cytogenetic analysis for MYC, IGH-BCL-2, and BCL-6 rearrangement in all our DLBCL cases to identify aggressive subtypes (presence of IGH-MYC, MYC rearrangement, or concomitant presence of MYC and IGH-BCL-2 and/or BCL-6 rearrangements) (33,34). We also demonstrate subclassification of low-grade NHL, using a combination of immunohistochemistry on cell block and flow cytometry into CLL-SLL, follicular lymphoma, mantle cell lymphoma, and marginal zone lymphoma (35)(36)(37). Moreover, adequate material was available after this multimodality testing approach for IGH-TCR gene rearrangement studies by polymerase chain reaction, when this was required.…”
Section: Discussionmentioning
confidence: 80%
“…Several studies have demonstrated the usefulness of FC in diagnosing lymphoma by means of fine needle aspiration (FNA) cytology as well as in staging and follow-up (18)(19)(20)(21)(22)(23)(24). However, only few reports are available regarding the role of FC in tissue diagnosis of lymphoma (25)(26)(27)(28)(29)(30)(31), and literature mainly reports tissue FC studies in selected lymphoma subtypes (12,14,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Ravinsky and Morales [40] found that a complete diagnosis could be reached in up to 82% of NHL cases. Recently, Zeppa et al [41], analyzing 446 cases of benign reactive hyperplasia and NHL, demonstrated that FNAC + flow cytometry are effective in the cytological diagnosis and classification of NHL with reproducible results. On the other hand, the exiguity of diagnostic material and clinicopathological limitations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the exiguity of diagnostic material and clinicopathological limitations (e.g. necrosis or fibrosis in the examined area, partial involvement) can represent an obstacle to further improvements of results [41]. Thus, a biopsy should be preferred, while FNAC could be performed in patients for whom excisional biopsy is contraindicated or for ancillary studies.…”
Section: Discussionmentioning
confidence: 99%